Image Processing for Quality Inspection of Mango Fruit - Usman Ahmad (Jurnal Keteknikan Pertanian, 2002)
Indonesia has many kinds of tropical fruits, including mango, that can be exported besides to suplly the demand on the fruits in the country. To ensure the quality of mango, it is important to do sortation and grading on them, especially those for export, based on the quality requirement. In this case, the use of high technology such as image processing in necesary to put into practise with the aim to increase the consistance of sortation and grading processes as compare to the result of manual work.